2019
DOI: 10.1103/physrevb.100.174514
|View full text |Cite
|
Sign up to set email alerts
|

Chiral p -wave superconductors have complex coherence and magnetic field penetration lengths

Abstract: We show that in superconductors that break time reversal symmetry and have anisotropy, such as p + ip materials, all order parameters and magnetic modes are mixed. Excitation of the gap fields produces an excitation of the magnetic field and vice versa. Correspondingly the long-range decay of the magnetic field and order parameter are in general given by the same exponent. Thus one cannot characterize p + ip superconductors by the usual coherence and magnetic field penetration lengths. Instead the system has n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 28 publications
(45 reference statements)
0
15
0
Order By: Relevance
“…In isotropic superconductors, domain walls are associated with zero magnetic field, unless the domain wall is attached to an inhomogeneous pinning center or there is an underlying density inhomogeneity [9,12,13]. However, in the presence of anisotropies, it has been shown that the magnetic field is coupled with phase difference gradients [15,[26][27][28] and with matter field density gradients [30]. This would suggest that anisotropies could principally alter the magnetic signatures of domain walls in s + is and s + id systems.…”
Section: Ginzburg-landau Formulationmentioning
confidence: 99%
“…In isotropic superconductors, domain walls are associated with zero magnetic field, unless the domain wall is attached to an inhomogeneous pinning center or there is an underlying density inhomogeneity [9,12,13]. However, in the presence of anisotropies, it has been shown that the magnetic field is coupled with phase difference gradients [15,[26][27][28] and with matter field density gradients [30]. This would suggest that anisotropies could principally alter the magnetic signatures of domain walls in s + is and s + id systems.…”
Section: Ginzburg-landau Formulationmentioning
confidence: 99%
“…II B. The decay of magnetic fields in this model usually involves multiple modes and multiple length scales [52], that yields further differences compared to s + is models previously studied in Monte Carlo simulations [36,37]. In what follows we will not distinguish between the subdominant electromagnetic scales.…”
Section: A Ginzburg-landau Modelmentioning
confidence: 98%
“…The London limit is commonly used for similar models [40,41]. However, in the case of a multicomponent order parameter, and with the addition of Ising anisotropy and MGT, such an approach requires considerable care and is generally not applicable [52].…”
Section: B London Limitmentioning
confidence: 99%
See 2 more Smart Citations